2017
DOI: 10.1007/s13340-017-0330-2
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of sitagliptin in elderly patients with type 2 diabetes mellitus and comparison of hypoglycemic action of concomitant medications: a subanalysis of the JAMP study

Abstract: Purpose To determine the efficacy and safety of sitagliptin when used with some therapeutic drugs to treat elderly patients. Methods Sitagliptin (50 mg/day) was added to the preexisting therapy for type 2 diabetes. Changes in the glycated hemoglobin (HbA1c) level after 3 months of treatment were compared with the baseline, and exploratory analysis was performed. These analyses were conducted as subanalyses of the JAMP study, which was an open-label observational study.Results For patients who were C65 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Our previous study of sitagliptin showed that eGFR decreased significantly in elderly subjects aged over 65; however, this parameter did not decrease in the patients with low baseline eGFR, although it decreased in the patients with high baseline eGFR [15]. Ujihara et al reported similar results [16]. Their study showed the eGFR change to be -2.7 ± 8.1 in elderly patients receiving sitagliptin for 3 months, a level similar to ours in the present study; it can be conjectured that there is no major difference in renal effects in the elderly between sitagliptin and alogliptin.…”
Section: Discussionmentioning
confidence: 78%
“…Our previous study of sitagliptin showed that eGFR decreased significantly in elderly subjects aged over 65; however, this parameter did not decrease in the patients with low baseline eGFR, although it decreased in the patients with high baseline eGFR [15]. Ujihara et al reported similar results [16]. Their study showed the eGFR change to be -2.7 ± 8.1 in elderly patients receiving sitagliptin for 3 months, a level similar to ours in the present study; it can be conjectured that there is no major difference in renal effects in the elderly between sitagliptin and alogliptin.…”
Section: Discussionmentioning
confidence: 78%
“…Such changes in renal function parameters after sitagliptin treatment are consistent with previous reports, including our own 27 , 33 . In fact, a previous study demonstrated that sitagliptin treatment decreased eGFR in older T2D patients with a high baseline eGFR, but not in those a low baseline eGFR 22 . Renal hemodynamic effects beyond glycemic control have been suggested for GLP-1-based therapies 34 .…”
Section: Discussionmentioning
confidence: 94%
“…In a randomized controlled study comparing treatment with sitagliptin and placebo, sitagliptin monotherapy did not cause hypoglycemia in 206 older T2D 40 . In an open-label observational study for older adults with T2D, there was no case of hypoglycemia after sitagliptin was added on to other oral anti-diabetic drugs, including sulfonylureas 22 . In the present study, we found that the incidence of hypoglycemia was not increased in sitagliptin group, which reinforces the evidence that sitagliptin is unlikely to cause severe hypoglycemic event in older adults with T2D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations